Hydroelectric Plants and Dams as Industrial Heritage in the Context of Nature-Culture Interrelation: An Overview of Examples in Turkey - Nurdan Kuban (Energies, 2021)
The article investigates nature–culture interrelation over the case studies of hydroelectric plants of the 20th century. In many cases, construction of these structures has evidently resulted in irreversible changes in natural and cultural environments. However, they have also supplied energy for the industrialization of civilizations. After approximately 100 years of existence, it is crucial to determine the future of these hydroelectric facilities, which are artifacts of industrial heritage approaching the end of their productive life spans. The article proposes an analytical approach aiming to sustain the integrity of nature and culture in the conservation of hydroelectric plants, presenting these energy facilities as cultural properties of industrial heritage, and discussing the impact of hydroelectric dams on natural and cultural environments, along with the effects of nature in the deterioration of these structures in order to pave the way to an optimized and sustainable future for the heritage of energy.